GATA3 Is a Useful Immunohistochemical Marker to Differentiate Variants of Renal Tubular Lesions from Different Segments of Renal Tubules. (28th October 2021) - Deebajah, M; Qu, Z; Zhang, P
Abstract: Introduction/Objective: GATA3 is found in glomerular mesangial cells, and the distal tubules & collecting ducts in metanephros and eventual kidneys, but not associated with the proximal tubules and loops of Henle. We hypothesize that GATA3 can be used as a marker to identify the origin of tubular differentiation in most renal tumors. Methods/Case Report: Ten negative controls and 43 renal mass lesions (RCC, papillary, clear cell papillary, and chromophobe carcinomas, oncocytoma, and polycystic kidney disease). GATA3 nuclear stain was graded as negative (absent stain), equivocal and positive (< 5 and > 5% cells, respectively). Details of their GATA3 nuclear expression was analyzed for identifying their tubular segmental origins. Results (if a Case Study enter NA): In 10 normal renal parenchyma, GATA3 was positive in mesangial cells, distal tubules, and collecting ducts, but was negative in the proximal tubules and loop of Henle. The cystic lining of glomerulocystic renal disease was stained negatively for GATA3 (proximal tubular origin), whereas pediatric and adult variants of polycystic kidney diseases was positive for GATA3 staining (distal tubular origin). 1/10 ten clear cell RCC and papillary RCC showed focal positive GATA3 stain. GATA3 showed weakly positive staining in some oncocytomas (4/11) and some chromophobe RCC (4/11), indicating that they might be derived from the junctional segment between the loop of Henle and the distal tubules. By contrast, all clear cell papillary RCC (distal tubule origin) were diffusely positive. Conclusion: Our results indicate that GATA3 is a useful immunohistochemical marker to determine the developmental origin in the specific renal tubular segment for the majority of renal mass lesions. Thus, it may be useful for routine differential diagnosis of these lesions.